2008
DOI: 10.1016/j.molcel.2007.11.027
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Decapping Is Promoted by an RNA-Binding Channel in Dcp2

Abstract: Cap hydrolysis by Dcp2 is a critical step in several eukaryotic mRNA decay pathways. Processing requires access to cap-proximal nucleotides and the coordinated assembly of a decapping mRNP, but the mechanism of substrate recognition and regulation by protein interactions have remained elusive. Using NMR spectroscopy and kinetic analyses, we show that yeast Dcp2 resolves interactions with the cap and RNA body using a bipartite surface that forms a channel intersecting the catalytic and regulatory Dcp1-binding d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
166
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(181 citation statements)
references
References 65 publications
(88 reference statements)
11
166
0
4
Order By: Relevance
“…1A; She et al 2006). The catalytic domain contains the active site and an interaction groove for the RNA body (Deshmukh et al 2008). The N-terminal domain serves two purposes: First, it enhances the activity of the catalytic domain by recognizing part of the mRNA cap structure (Floor et al 2010), and secondly, it directly interacts with the decapping activator Dcp1 (She et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1A; She et al 2006). The catalytic domain contains the active site and an interaction groove for the RNA body (Deshmukh et al 2008). The N-terminal domain serves two purposes: First, it enhances the activity of the catalytic domain by recognizing part of the mRNA cap structure (Floor et al 2010), and secondly, it directly interacts with the decapping activator Dcp1 (She et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the involvement of Dcp1a in cellular signaling pathways through protein-protein interactions (36,37). All eukaryotic orthologues of Dcp1a contain an N-terminal EVH1 (enabled vasodilator-stimulated protein homology 1) domain (30,31,37,38). EVH1 domains are known to interact with a variety of proline-rich protein ligands (39 -41).…”
mentioning
confidence: 99%
“…Yeast DCP2 interacts directly with DCP1 and this interaction is required for decapping in vivo and in vitro (3)(4)(5)(6)(7). In humans, the DCP2-DCP1 interaction requires additional proteins, which together assemble into multimeric decapping complexes that also include the enhancers of decapping 3 and 4 (EDC3 and ECD4), and the DEAD-box protein DDX6/RCK (8,9).…”
mentioning
confidence: 99%
“…In humans, the DCP2-DCP1 interaction requires additional proteins, which together assemble into multimeric decapping complexes that also include the enhancers of decapping 3 and 4 (EDC3 and ECD4), and the DEAD-box protein DDX6/RCK (8,9). DCP2 is highly conserved and most information on DCP2 activation stems mainly from studies in S. cerevisiae and S. pombe (3)(4)(5)(6)(7). Fungi, however, lack EDC4 as well as many extensions and additional domains present in decapping activators of metazoan orthologs (8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation